Association of Fusobacterium nucleatum infection with colorectal cancer in Kazakhstani patients - Kulmambetova, Gulmira; Kurentay, Botakoz; Gusmaulemova, Alua; Utupov, Talgat; Auganova, Dana; Tarlykov, Pavel; Mamlin, Meiram; Khamzina, Saule; Shalekenov, Sanzhar; Kozhakhmetov, Arman (Frontiers in Oncology, 2024)
ObjectivesFusobacterium nucleatum is a gram-negative anaerobic bacillus associated with colorectal cancer (CRC). We aimed to determine the abundance of F. nucleatum and other CRC-associated bacteria using quantitative real-time polymerase chain reaction (qPCR) analysis to detect the possible correlations between tumor and normal tissues and the relationships between patients’ clinical characteristics, diet, and CRC-associated bacteria.MethodsA total of 249 biopsy samples of tumor and paired normal tissues were collected from patients with CRC. Biopsy samples were screened for detection of F. nucleatum using qPCR targeting nusG gene. Bacteroides fragilis, Escherichia coli, and Streptococcus gallolyticus were also detected in the samples using species-specific genes.ResultsThe frequencies of detection of F. nucleatum in the tumor and normal tissues of patients with CRC were 43.37 and 24.1%, respectively (P < 0.05). Statistical analysis using cycle threshold (Ct) values from qPCR data and clinical characteristics showed that tumor size, tumor location, and processed meat consumption were significantly correlated with the abundance of F. nucleatum (P < 0.05). The significance of the prevalence of B. fragilis and E. coli in tumor tissues was marginally higher than that in normal tissues (P < 0.1), and the consumption of processed/red meat affected the prevalence of these bacteria (P < 0.05).ConclusionsOur results showed an association between the presence of F. nucleatum in tumor tissues and CRC, indicating that F. nucleatum may be a potential marker for CRC diagnosis. F. nucleatum is enriched in CRC tissues and is associated with CRC development.